Interest of RT-PCR in the Diagnosis and Follow-Up of Patients with Chronic Myeloid Leukemia (A Study in Western Algeria) - Liamani, Ouafia; Hayet, Kortiche; Nadjet, Siali; Rabha, Mellah (Asian Pacific Journal of Cancer Care, 2025)
Background: This prospective study evaluated the implementation of RT-PCR for the molecular monitoring of chronic myeloid leukemia (CML) patients at Sidi Bel Abbès University Hospital. Methods: We analyzed 31 consecutive CML patients (mean age 50 years, range 31–72). All patients carried the b3a2 fusion transcript. The Sokal risk distribution was as follows: high (6.45%), intermediate (51.61%), and low (41.93%). Molecular response was assessed by the *BCR-ABL1/ABL1* ratio (IS%) at diagnosis and during treatment follow-up. Results: The median BCR-ABL1/ABL1 ratio declined to 3.45% (IQR 0.66–19) at 3 months (n=12), 0.37% (IQR 0.00028–23) at 6 months (n=29), and 0.01% (IQR 0.00021–12) at 18 months (n=14). MMR rates were significantly higher in patients achieving a ratio of ≤10% at 3 months (83.3% vs. 19.0%, p<0.001) and ≤1% at 6 months (69.0% vs. 28.0%, p<0.001). Only one patient (3.2%, 95% CI 0–9.3) without an early molecular response achieved MMR by 18 months. Conclusions: Our findings confirm the clinical utility of RT-PCR for CML monitoring and emphasize the prognostic importance of early molecular response, particularly at the 3- and 6-month timepoints, in Algerian patients.